Nr4a2 Transcription Factor in Hippocampal Synaptic Plasticity, Memory and Cognitive Dysfunction: A Perspective Review - Català-Solsona, Judit; Miñano-Molina, Alfredo J.; Rodríguez-Álvarez, José (Frontiers in Molecular Neuroscience, 2021)
Long-lasting changes of synaptic efficacy are largely mediated by activity-induced gene transcription and are essential for neuronal plasticity and memory. In this scenario, transcription factors have emerged as pivotal players underlying synaptic plasticity and the modification of neural networks required for memory formation and consolidation. Hippocampal synaptic dysfunction is widely accepted to underlie the cognitive decline observed in some neurodegenerative disorders including Alzheimer’s disease. Therefore, understanding the molecular pathways regulating gene expression profiles may help to identify new synaptic therapeutic targets. The nuclear receptor 4A subfamily (Nr4a) of transcription factors has been involved in a variety of physiological processes within the hippocampus, ranging from inflammation to neuroprotection. Recent studies have also pointed out a role for the activity-dependent nuclear receptor subfamily 4, group A, member 2 (Nr4a2/Nurr1) in hippocampal synaptic plasticity and cognitive functions, although the underlying molecular mechanisms are still poorly understood. In this review, we highlight the specific effects of Nr4a2 in hippocampal synaptic plasticity and memory formation and we discuss whether the dysregulation of this transcription factor could contribute to hippocampal synaptic dysfunction, altogether suggesting the possibility that Nr4a2 may emerge as a novel synaptic therapeutic target in brain pathologies associated to cognitive dysfunctions.